1978
DOI: 10.1139/y78-127
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies on the pulmonary vein of the horse. I. Effects of selected spasmogens

Abstract: Horses suffer from a respiratory condition, similar to human allergic asthma, that is characterized by severe dyspnea, wheezing, coughing, and mucus production. Mediator substances released during the allergic reaction may contract airways and pulmonary vasculature. Nothing is known of the effects of autacoids and other vasoactive substances on equine pulmonary vessels. Therefore, spiral strips of equine pulmonary vein were prepared in vitro and the effects of histamine (H), 5-hydroxytryptamine (5HT), bradykin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The antagonism of methysergide to 5-HT-induced contractile responses of goat pulmonary arteries demonstrates the existence of classical D receptors in this tissue. This observation is not inconsistent with similar findings in the pulmonary blood vessels of several other mammalian species (Somlyo & Somlyo, 1970;Eyre, 1971Eyre, , 1975aJoiner et al, 1975;Su & Bevan, 1976;Hanna & Eyre, 1978;Chand & Altura, 1980). 5-HT-induced relaxations of the goat pulmonary veins were not blocked by indomethacin (a potent blocker of prostaglandin (Eyre, 1975a;Feniuk et al, 1979;Chand & Altura, 1980).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The antagonism of methysergide to 5-HT-induced contractile responses of goat pulmonary arteries demonstrates the existence of classical D receptors in this tissue. This observation is not inconsistent with similar findings in the pulmonary blood vessels of several other mammalian species (Somlyo & Somlyo, 1970;Eyre, 1971Eyre, , 1975aJoiner et al, 1975;Su & Bevan, 1976;Hanna & Eyre, 1978;Chand & Altura, 1980). 5-HT-induced relaxations of the goat pulmonary veins were not blocked by indomethacin (a potent blocker of prostaglandin (Eyre, 1975a;Feniuk et al, 1979;Chand & Altura, 1980).…”
Section: Discussionsupporting
confidence: 85%
“…5 5-HT-induced arterial contractile responses were antagonized by methysergide, showing the occurrence of classical D receptors in the goat pulmonary artery. 6 It is concluded that differential reactivity of pulmonary arteries and veins to vasoactive agents may play differential role(s) in the pathophysiology inflammatory activity in goat pulmonary veins.Recently, there has been some interest in the autonomic and autacoid pulmonary pharmacology of farm animals (Eyre, 1971; 1975,a,b;Hanna & Eyre, 1978; Chand, DeRoth & Eyre, 1979;Chand & Altura, 1980). During the course of one of these investigations, 5-hydroxytryptamine (5-HT) was found to relax goat trachea (Chand et al, 1979).…”
mentioning
confidence: 99%
“…However, Eyre and Lewis (1973) demonstrated an increase in kinin production in horse blood during experimentally-induced anaphylactic responses. Prostaglandins and kinins are described as secondary mediators of inflammation because they are airway smooth muscle of horses (Hanna and Eyre 1978). 5-Hydroxyfrypfamine.…”
Section: Chemical Mediators Of Antibody-dependent Hypersensitivitymentioning
confidence: 99%
“…23) Histamine is also reported to exert pulmonary vasodilator actions preferentially during vasoconstriction and in other conditions of high PAP in animals [18][19][20] including rats. 20,24) However, our study showed no changes in PVR in response to histamine, indicating that histamine did not cause pulmonary vasoconstriction or vasodilatation in in vivo rat lungs.…”
Section: Discussionmentioning
confidence: 99%